DNA free CRISPR/DCAS9 based transcriptional activation system for UGT76G1 gene in Stevia rebaudiana Bertoni protoplasts - Ghose, Asish Kumar; Abdullah, Siti Nor Akmar; Md Hatta, Muhammad Asyraf; Megat Wahab, Puteri Edaroyati (MDPI, 2022)
The UDP-glycosyltransferase 76G1 (UGT76G1) is responsible for the conversion of stevioside to rebaudioside A. Four single guide RNAs (sgRNAs) were designed from the UGT76G1 proximal promoter region of stevia by using the online-based tool, benchling. The dCas9 fused with VP64 as a transcriptional activation domain (TAD) was produced and purified for the formation of ribonucleoproteins (RNPs) by mixing with the in vitro transcribed sgRNAs. Protoplast yield was the highest from leaf mesophyll of in vitro grown stevia plantlets (3.16 × 106/g of FW) using ES5 (1.25% cellulase R-10 and 0.75% macerozyme R-10). The RNPs were delivered into the isolated protoplasts through the Polyethylene glycol (PEG)-mediated transfection method. The highest endogenous activation of the UGT76G1 gene was detected at 27.51-fold after 24 h of transfection with RNP30 consisting of CRISPR/dCas9-TAD with sgRNA30 and a similar activation level was obtained using RNP18, RNP33, and RNP34, produced using sgRNA18, sgRNA33, and sgRNA34, respectively. Activation of UGT76G1 by RNP18 led to a significant increase in the expression of the rate-limiting enzyme UGT85C2 by 2.37-fold and there was an increasing trend in the expression of UGT85C2 using RNP30, RNP33, and RNP34. Successful application of CRISPR/dCas9-TAD RNP in activating specific genes can avoid the negative integration effects of introduced DNA in the host genome.